Pelaksanaan Metode One Day One Ayat (Satu Hari Satu Ayat) dalam Menghafal Al-Qur’an di Pondok Pesantren Madinatul Qur’an Betung - Maruyati, Anti; Astuti, Mardiah; Hidayat, Hidayat (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to describe the implementation of the One Day One Ayat method for memorizing the Qur'an at the Madinatul Qur'an Islamic Boarding School. This research employs field research with a qualitative approach. The subjects of this study include 12 informants, consisting of ustadz (male teachers), ustadzah (female teachers), and students of the Madinatul Qur'an Islamic Boarding School. The data collection techniques used in this study are observation, interviews, and documentation. The analysis results show that the targets and objectives set for the implementation of the One Day One Ayat method for memorizing the Qur'an have been successfully achieved. By using the one day one verse method, children find it easier to memorize, do not feel burdened, and do not experience difficulties in memorizing. The children can also apply this method to memorize the Qur'an. Thus, the goals or targets for memorizing the Qur'an using this method can be achieved effectively